Immature Platelets and Risk of Cardiovascular Events among Patients with Ischemic Heart Disease: A Systematic Review - Faber, Julie; Hvas, Anne-Mette; Kristensen, Steen Dalby; Grove, Erik Lerkevang; Adelborg, Kasper (Thrombosis and Haemostasis, 2020)
Background Immature platelets are larger and may be more thrombogenic than mature platelets. This systematic review included studies on the association between mean platelet volume (MPV), immature platelet count (IPC), and immature platelet fraction (IPF) and the risk of major cardiovascular events (MACEs) in patients with acute coronary syndrome (ACS) or stable coronary artery disease (CAD).Methods The literature search included studies in PubMed, Embase, Web of Science, and Cochrane Library. The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Effect estimates that included multivariate adjusted odds ratios, relative risks, or hazard ratios were extracted.Results Forty-two studies were identified. High MPV was positively associated with MACE in 20 of 26 studies of patients with ACS, four of five studies in patients with stable CAD, and in all six studies comprising a combined population with ACS and stable CAD. Using continuous models of MPV in patients with ACS, effect estimates varied from 0.90 (95% confidence interval [CI]: 0.95–1.03) to 1.66 (95% CI: 1.32–2.09). The strength of these associations was broadly similar among patients with stable CAD and in combined populations. Five studies investigated IPC or IPF as exposures and all reported positive associations with MACE among patients with ACS, stable CAD, or in combined populations.Conclusion This review demonstrated clear evidence for positive associations between measures of immature platelets and subsequent risk of MACE in acute and stable ischemic heart disease patients.
Keywords: acute coronary syndrome; coronary artery disease; immature platelets; mean platelet volume